Effects of Physical Activity on Anthropometric Characteristics in School-Age Children: A Review Study (Baltic Journal of Sport and Health Sciences, 2021)
Background. Today, it is very speculative  to talk about the percentage of obese children in the world because these figures change significantly from day to day, and there are even significant differences between respondents in the same country, according to geographical area and place of residence. A constant decline in the level of physical activity of children on a global level can be reported from the age when they start school. Energy intake of food is largely from energy consumption, which leads to an increase in body weight and obesity. Factors of overweight and obesity are associated with a sensitive comparison of health: a significantly increased risk of diabetes, disorders of the locomotor system, and increased social and psychological rights.Methods and results. During the systematization of the research on the topic, the aim of the paper was to determine whether the influence of physical activity on anthropometric parameters in school-age children is reviewed by previous research. Nineteen types of studies were collected. The following electronic databases were used to search the literature: MEDLINE, SCOPUS, Web of Science SPORTS DISCUS in the period from 2004 to 2016. The respondents included in the research were school-age children.Conclusion. The positive impact of various physical activity programs is aimed at reducing the parameters of anthropometric characteristics and obesity prevention.Keywords: physical activity, school program, morphology, anthropomeric data, exercises.